2018
DOI: 10.1097/aog.0000000000002423
|View full text |Cite
|
Sign up to set email alerts
|

Preterm Delivery and Low Birth Weight Among Neonates Conceived With Intracytoplasmic Sperm Injection Compared With Conventional In Vitro Fertilization

Abstract: Rates of preterm delivery and LBW were similar between pregnancies conceived with ICSI and conventional IVF after propensity score matching and stratifying by baseline patient characteristics. Previously reported differences in these outcomes were likely secondary to patients' inherent risk factors rather than the fertilization procedure itself.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…At the same time, we noticed that the rate of multiple pregnancies in the frozen sperm group was 5% higher than that of the fresh group. As LBW is a known complication of multiple pregnancies (21,22), and our study also showed that LBW is significantly related to single or Newborns in two groups twin pregnancies, we investigated the incidence of LBW in twin and single pregnancy separately. Our final results demonstrated that the rates of LBW in twin pregnancy and single pregnancy between the two groups were similar.…”
Section: Discussionmentioning
confidence: 91%
“…At the same time, we noticed that the rate of multiple pregnancies in the frozen sperm group was 5% higher than that of the fresh group. As LBW is a known complication of multiple pregnancies (21,22), and our study also showed that LBW is significantly related to single or Newborns in two groups twin pregnancies, we investigated the incidence of LBW in twin and single pregnancy separately. Our final results demonstrated that the rates of LBW in twin pregnancy and single pregnancy between the two groups were similar.…”
Section: Discussionmentioning
confidence: 91%
“…showed that there was a lower risk of PTD in ICSI singletons than in IVF singletons, indicating that the fertilization procedure might have an effect on this perinatal outcome ( 12 ). Nevertheless, other work described that the reason behind this difference was that the high risk of PTD in IVF singletons might be secondary to female inherent risk factors instead of IVF itself ( 9 ). Although the type of IVF/ICSI treatment might not affect PTD, we found women with GnRH-antagonist protocol had higher risk to deliver a preterm baby, while women with GnRH-agonist protocol had lower risk.…”
Section: Discussionmentioning
confidence: 99%
“…However, data available by Keyhan et al. did not support this finding ( 9 ). No increasing risk of PTD was observed by Keyhan et al.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…The above situation is more prominent in multiple pregnancies. LBW is a known complication of multiple gestation [20]. A recently published research revealed that mothers with multiple pregnancies were at a signi cantly increased risk of delivering babies with LBW, both in the case of preterm and term birth [21].…”
Section: Discussionmentioning
confidence: 99%